An outlook of FMC's current and future herbicide‐resistance management strategies. Issue 4 (3rd May 2020) - Ganie, Zahoor A; Obrigawitch, Timothy; Kang, Il‐Ho; Copeland, Drake; Gutteridge, Steven; May, John; Schrage, Brandon; Albright, Robert; Chandi, Aman
Abstract: Herbicide resistance has emerged globally as a serious threat to profitable crop production. FMC promotes integrated weed management approaches including responsible use of existing herbicides, use of non‐herbicide weed control tools, awareness about herbicide resistance issues, and support to herbicide resistance management initiatives. FMC is dedicated to developing sustainable weed control solutions through the discovery of new herbicides with novel sites‐of‐action, effective formulations, advanced application technology, and proactive monitoring for herbicide resistance. © 2020 Society of Chemical Industry Abstract : Herbicide resistance has emerged globally as a serious threat to profitable crop production. FMC promotes integrated weed management approaches including responsible use of existing herbicides, use of non‐herbicide weed control tools, awareness about herbicide resistance issues, and support to herbicide resistance management initiatives.